The pavement performance of concrete prepared with molybdenum tailings - Dongliang Kuang; Heng Meng; Bo Liu; Jincheng Yu; Tao Wang; Huaxin Chen (Case Studies in Construction Materials)
Molybdenum tailings (MT) are solid wastes discharged from molybdenum mines after mining and sorting. At present, accumulation is still the primary treatment method of MT, which causes great harm to the environment. If MT can be used to prepare cement concrete pavement for low-grade roads, its utilization rate could be significantly improved. In this paper, various MT contents were substituted for natural sand to prepare pavement concrete. The influence of MT content on concrete pavement performance was studied using working performance, mechanical property, dry shrinkage property, wear resistance test, impermeability test, and microstructure characterization of concrete. The results showed that with increasing MT content in pavement concrete, the fluidity decreased and the dry shrinkage rate increased gradually. An appropriate dosage of MT in pavement concrete could improve its flexural strength, compressive strength, wear resistance and impermeability, which could be attributed to the promotion of cement hydration, improvement of pore structure and increase of concrete density. When the content of MT is 25 %, the flexural strength and compressive strength of concrete at 28 d reached the highest values of 5.92 MPa and 46.3 MPa, respectively, with the relative permeability coefficient of 1.64 × 10−9 mm/s and the wear loss of only 1.80 kg/m2. Considering the pavement performance of concrete and the utilization rate of MT, in theory, 100 % MT concrete may be used for the construction of low-elevation high-altitude pavements. Low-grade roads, characterized by comparatively low performance requirements for cement concrete, provide an opportunity to enhance the utilization rate of MT.